EVALUASI METODE PERHITUNGAN KETEBALAN PERISAI PADA RUANG DIGITAL RADIOGRAFI - Wulandhari Wulandhari; Wahyu Setia Budi; Agung Dwiyanto (Youngster Physics Journal, 2015)
This research would discuss about the methods to determine shielding thickness for X-Ray of digital radiography room published by BIR (British Institute of Radiology), NCRP (National Council on Radiation Protection), KEMENKES No.1014/Menkes/SK/XI/2008 and Perka BAPETEN No. 4 (2013). Each method assume different considerations so evaluation is needed in terms of it’s ability to control external radiation exposure.                Shielding thickness based on NCRP and BIR need data such as space map area of the other side operation X-Ray, shift workers, total number of patient, and distance of primary and secondary radiation to the point of occupation, all of data collected based on survey before experiment. Then shielding thickness calculated  based on the dose rate inside and outside room be used as a comparation.                 The result  of primary Pb shielding thickness by NCRP 49 is 1,00  mm, NCRP 147 is 0,469 mm and BIR is amount of 0,650 mm. The secondary Pb thickness shielding by NCRP 49 is 0,500 mm, NCRP 147 is 0,170 mm and BIR is amount of 0,00980 mm. Shielding thickenss based on dose rate, for primary Pb shielding thickness is  0,898 mm and secondary Pb shielding thickness is 0,987 mm respectivelly. The result of shielding thickness based on NCRP 49 method is closer with the result by shielding thickness was based on dose rate. Keywords: NCRP 49, NCRP 147, BIR, Shielding Thickness, Dose Rate.